Murder of innocence [compact disc, unabridged] : true-crime thrillers - Patterson, James, 1947-; DiLallo, Max; Bourelle, Andrew (Hachette Book Group, 2020)
Murder of Innocence: It's impossible to resist Andrew Luster. He's rich, charming, and good-looking, and dozens of women have fallen under his spell. But Andrew is no mere womanizer. He's a predator, and it'll take a global effort to put him behind bars.